What is new about the new literacies of online reading comprehension - Donald J. Leu; Lisa Zawilinski; Jill Castek; Manju Banerjee; Brian C. Housand; Yingjie Liu; Maureen O’Neil (Secondary School Literacy: What Research Reveals for Classroom Practice, 2013)
Change defines literacy (Coiro, 2003; Hartman, 2000; Leu, 2000; Rosenblatt, 1938). Our lives change in fundamental ways as we become literate, expanding access to information, communication, and action (Freire, 1972, 1985; LeVine, LeVine, & Schnell, 2001). Because understanding change is at the core of what we do, it is ironic that our research community has largely ignored the extensive changes to literacy taking place in a digital, networked, multimodal, and multitasking world of information and communication. The nature of literacy is undergoing profound change, and we have little research or solid theory to inform our understanding of the consequences for classroom practice (Reinking, 1998).
Keywords: éducation; jeunesse; lecture numérique; multimodalité; pédagogie

New Literacies of Online Reading Comprehension - Donald J. Leu; Heidi Everett-Cacopardo; Lisa Zawilinski; Greg McVerry; W. Ian O'Byrne (2012)

Using peer collaboration to support online reading, writing, and communication: An empowerment model for struggling readers - Laurie A. Henry; Jill Castek; W. Ian O'Byrne; Lisa Zawilinski (Reading & Writing Quarterly, 2012)
This comparative case study investigated the implementation of an empowerment model for struggling readers that utilized the Internet as a context for reading, writing, and communicating in 3 different classroom contexts. Through student-centered techniques, such as flexible grouping and peer teaching, we designed Internet Reciprocal Teaching to support the development of the new literacies of online reading comprehension among elementary and middle school students. Results suggest that peer collaboration was the primary means of strategy exchange and that students who were previously perceived as struggling readers became active in coaching, leading, and sharing new strategies. In effect, peer collaboration appeared to reconceptualize struggling readers' role in the classroom and set the context for greater engagement in literacy activities and investment in learning.
Keywords: collaboration; école primaire; école secondaire; écriture et lecture numériques; lecture numérique; pratiques pédagogiques